2020
DOI: 10.4103/ijo.ijo_1528_20
|View full text |Cite
|
Sign up to set email alerts
|

A new normal with cataract surgery during COVID-19 pandemic

Abstract: Cataract is the second leading cause of preventable blindness on the globe. Several programs across the country have been running efficiently to increase the cataract surgical rates and decrease blindness due to cataract. The current COVID-19 pandemic has led to a complete halt of these programs and thus accumulating all the elective cataract procedures. At present with the better understanding of the safety precautions among the health care workers and general population the Government of India (GoI) has give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
(20 reference statements)
0
30
0
1
Order By: Relevance
“…19 The popularity of cataract surgery and IOL implantation has increased exponentially in India over the past two decades. [20][21][22] Demand for multifocal IOLs is expected to surge globally due to: the large number of cataract surgeries (∼26 million cataract surgeries performed in 2017); changing socioeconomic frameworks; the world's aging population; improvements in healthcare sectors and expenditure; increased demand for spectacle independence; access to innovative, advanced IOLs; and increased patient awareness. 15 Although previous clinical investigations have demonstrated a continuous range of vision from near to distance with TFNT00, 14,[23][24][25][26][27][28] to date, no clinical studies have been conducted in Indian patients.…”
Section: Introductionmentioning
confidence: 99%
“…19 The popularity of cataract surgery and IOL implantation has increased exponentially in India over the past two decades. [20][21][22] Demand for multifocal IOLs is expected to surge globally due to: the large number of cataract surgeries (∼26 million cataract surgeries performed in 2017); changing socioeconomic frameworks; the world's aging population; improvements in healthcare sectors and expenditure; increased demand for spectacle independence; access to innovative, advanced IOLs; and increased patient awareness. 15 Although previous clinical investigations have demonstrated a continuous range of vision from near to distance with TFNT00, 14,[23][24][25][26][27][28] to date, no clinical studies have been conducted in Indian patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cataract is the second leading cause of preventable vision impairment. [ 9 10 ] Most common cataract operated in the post-lockdown period in our survey was mature cataract, which signifies postponement of less visually impairing forms of cataract by both patients and ophthalmic surgeons. A report on the impact of lockdown on elective surgical procedures estimated that 5.8 lakh elective surgeries (including all medical specialties) were postponed in India by May 2020 leading to increased complications and mortality.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, virtual care for patients with lower-risk disease is an ideal way to lower patient volume in clinic, waiting room occupancies, and risk of receiving in-person care for high-risk patients. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, virtual care for patients with lower-risk disease is an ideal way to lower patient volume in clinic, waiting room occupancies, and risk of receiving in-person care for high-risk patients. 17,18 Kruse and colleagues conducted a systematic review of telehealth and patient satisfaction and found that ease of use, low cost and decreased travel time are aspects of telemedicine that contribute to increased satisfaction. 9 Low cost can refer not only to the visit cost itself, but also to the relatively lower opportunity cost of not having to miss work or force a family member/friend to accompany the patient to the appointment.…”
Section: Discussionmentioning
confidence: 99%